How previous epidemics enable timelier COVID-19 responses: an empirical study using organisational memory theory - Sian Hsiang-Te Tsuei (BMJ Global Health)
Introduction There has been little systematic exploration into what affects timeliness of epidemic response, despite the potential for earlier responses to be more effective. Speculations have circulated that previous exposure to major epidemics helped health systems respond more quickly to COVID-19. This study leverages organisational memory theory to test whether health systems with any, more severe, or more recent exposure to major epidemics enacted timelier COVID-19 policy responses.Methods A data set was constructed cataloguing 846 policies across 178 health systems in total, 37 of which had major epidemics within the last 20 years. Hypothesis testing used OLS regressions with World Health Organization region fixed effects, controlling for several health system expenditure and political variables.Results Results show that exposure to any major epidemics was associated with providing earlier response in the following policy categories: all policies, surveillance/response, distancing, and international travel policies. The effect was about 6–10 days earlier response. The significance of this variable was largely nullified with the addition of the other two independent variables. Neither total cases nor years since previous epidemics showed no statistical significance.Conclusion This study suggests that health systems may learn from past major epidemics. Policymakers ought to institutionalise lessons from COVID-19. Future studies can examine specific generalisable lessons and whether timelier responses correlated with lower health and economic impacts.